2019
DOI: 10.4314/ijs.v21i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal profiles and microbial counts of selected sachet water brands in Birnin Kebbi Metropolis, Nigeria

Abstract: (£ 50 cfu ml). These results showed the water samples were seriously contaminated, and the water brands could pose a significant public health risk to the consumers in the city if this trend continues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Five (10%) of the studies reported assessing microbial contamination more than once [34–38] while the majority assessed this only once. Of the 52 included studies: two provided data on E. coli contamination only [39,40] eight assessed total coliforms only [34,37,41–46] sixteen assessed total coliforms and E. coli [10,35,36,47–59] fifteen characterised other bacteria in addition to E. coli [20,60–63]; total coliforms [38,64–66]; or total coliforms and E. coli [67–72] one study assessed TTC, total coliforms and E. coli [73] six other studies enumerated and characterised faecal coliform at 44–44.5°C within 48 h and we extracted the data as TTC [74,75], in addition to the total coliforms data reported [76–80]. two other studies also enumerated faecal coliform, however these were not characterised at the appropriate temperature [81,82].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five (10%) of the studies reported assessing microbial contamination more than once [34–38] while the majority assessed this only once. Of the 52 included studies: two provided data on E. coli contamination only [39,40] eight assessed total coliforms only [34,37,41–46] sixteen assessed total coliforms and E. coli [10,35,36,47–59] fifteen characterised other bacteria in addition to E. coli [20,60–63]; total coliforms [38,64–66]; or total coliforms and E. coli [67–72] one study assessed TTC, total coliforms and E. coli [73] six other studies enumerated and characterised faecal coliform at 44–44.5°C within 48 h and we extracted the data as TTC [74,75], in addition to the total coliforms data reported [76–80]. two other studies also enumerated faecal coliform, however these were not characterised at the appropriate temperature [81,82].…”
Section: Resultsmentioning
confidence: 99%
“…• two provided data on E. coli contamination only [39,40] • eight assessed total coliforms only [34,37,[41][42][43][44][45][46] • sixteen assessed total coliforms and E. coli [10,35,36,[47][48][49][50][51][52][53][54][55][56][57][58][59] • fifteen characterised other bacteria in addition to E. coli [20,[60][61][62][63]; total coliforms [38,[64][65][66]; or total coliforms and E. coli [67][68][69][70][71][72] • one study assessed TTC, total coliforms and E. coli [73] • six other studies enumerated and characterised faecal coliform at 44-44.5°C within 48 h and we extracted the data as TTC [74,75], in addition to the total coliforms data reported [76][77]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The effects of adsorbents (ACDW and LFB) on the structure of the bacterial communities in real aquaculture wastewater effluent after ammonia removal were examined. According to Yahaya et al [ 42 ], the bacterial count was examined in five treatments (samples): (1) filtered lipid-free biomass (LFB), (2) aquaculture wastewater treated with LFB (LFB-RAW), (3) filtered complete dry biomass (ACDW), (4) aquaculture wastewater treated with ACDW (ACDW-RAW), and (5) an aquaculture wastewater (RAW) sample that was not treated with A. platensis as a control. Sterile nutrient agar media was prepared by autoclaving at 120 °C for 20 min; 1 g·mL −1 of each sample was inoculated using pouring technique.…”
Section: Methodsmentioning
confidence: 99%
“…The most common group of contaminants in water is heavy metals (Kinuthia et al, 2020). The commonly detected heavy metals in water include arsenic, cadmium, chromium, copper, lead, nickel, and zinc (Yahaya et al, 2019;Moruf and Durojaiye, 2020). Although lagoon heavy metal pollution is less obvious and more direct than other types of pollution, it has far-reaching consequences for the aquatic ecosystem and humans (Okunade et al, 2021).…”
Section: Introductionmentioning
confidence: 99%